Cucurbitacins: elucidation of their interactions with the cytoskeleton - Wang, Xiaojuan; Tanaka, Mine; Peixoto, Herbenya; Wink, Michael (PeerJ, 2017)
Cucurbitacins, a class of toxic tetracyclic triterpenoids in Cucurbitaceae, modulate many molecular targets. Here we investigated the interactions of cucurbitacin B, E and I with cytoskeletal proteins such as microtubule and actin filaments. The effects of cucurbitacin B, E and I on microtubules and actin filaments were studied in living cells (Hela and U2OS) and in vitro using GFP markers, immunofluorescence staining and in vitro tubulin polymerization assay. Cucurbitacin B, E and I apparently affected microtubule structures in living cells and cucurbitacin E inhibited tubulin polymerization in vitro with IC50 value of 566.91 ± 113.5 µM. Cucurbitacin E did not affect the nucleation but inhibited the growth phase and steady state during microtubule assembly in vitro. In addition, cucurbitacin B, E and I all altered mitotic spindles and induced the cell cycle arrest at G2/M phase. Moreover, they all showed potent effects on actin cytoskeleton by affecting actin filaments through the depolymerization and aggregation. The interactions of cucubitacin B, E and I with microtubules and actin filaments present new insights into their modes of action.
Gesehen am 28.07.2017